2021
DOI: 10.1108/jedt-11-2020-0447
|View full text |Cite
|
Sign up to set email alerts
|

Strategic planning to investigate the decision index of organization for effective total quality management implementation – in context of Indian small and medium enterprises

Abstract: Purpose The aim of this paper is to present an empirical assessment and strategic planning for measuring the impact of total quality management (TQM) practices on small and medium enterprises (SMEs) and its effectiveness for business excellence. The authors investigate the present status of quality system in SMEs and find the thrust areas for TQM implementation in SMEs of strengths, weaknesses, opportunities and threats analysis. Also, it examines the effect of external environment on internal factors of SMEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Therefore, WM requires more improvements in manufacturing and service enterprises (Rehman et al 2018 ). In SMEs, Toke and Kalpande ( 2021 ) found that waste reduction has the least priority. Similarly, Kasseeah ( 2020 ) affirmed that not all small enterprises implemented strategies such as reusing empty bags, composting waste, and separating waste for recycling.…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, WM requires more improvements in manufacturing and service enterprises (Rehman et al 2018 ). In SMEs, Toke and Kalpande ( 2021 ) found that waste reduction has the least priority. Similarly, Kasseeah ( 2020 ) affirmed that not all small enterprises implemented strategies such as reusing empty bags, composting waste, and separating waste for recycling.…”
Section: Review Findingsmentioning
confidence: 99%
“…Lean and six sigma strategy is vital for managing waste and improving quality of products in MSMEs (Gupta et al 2022 ; Singh and Rathi 2021 ). In this vein, lean and six sigma model and total quality management strategies are important for SMEs to enhance sustainability, manage waste, enhance productivity, and improve quality of products (Lande et al 2019 ; Sodhi et al 2020a ; Toke and Kalpande 2021 ). The implementation of lean and six sigma strategy is positively influenced by effective leadership, reward and recognition system, the need for change, financial capabilities, and teamwork (Singh and Rathi 2021 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Small businesses must have a policy of addressing client needs through customer-focused activities. It is envisaged that QM policy and practice will aid this endeavour (Al-Gasawneh et al, 2021;Toke & Kalpande, 2021). According to previous research, prioritising the needs of the customer has a positive impact on operational performance (Ahire et al, 1996;Tarí & Claver, 2008), innovation performance (Kim et al, 2012), inventory management performance (Phan et al, 2011), customer satisfaction (Forza & Filippini, 1998;Phan et al, 2011;Tarí & Claver, 2008) and the overall firm's performance (Joiner, 2007).…”
Section: Customer Focus and Project Performancementioning
confidence: 99%
“…Research studies have been conducted to demonstrate the importance of quality management initiatives for small and medium-sized businesses (SMEs), which are considered the backbone of the economy (Mamman et al, 2019). Some other examples are TQM implementation in SMEs in Iran (Mehrabioun Mohammadi et al, 2021), India (Toke & Kalpande, 2021), Oman (Karyamsetty, 2021), and Kuwait (Sawaean & Ali, 2020). These studies have confirmed the importance of total quality management elements in enhancing the performance of any SMEs.…”
Section: Introductionmentioning
confidence: 96%
“…TQM is considered a powerful tool for achieving higher product standards, pursue business strategies and gaining a competitive advantage through strategic continuous improvement practices (Gupta et al, 2020;Jimoh et al, 2018;Toke and Kalpande, 2021;Yu et al, 2017).…”
Section: Tqm and Tpmmentioning
confidence: 99%